Salesian Oratory in Italy - Integration of Foreign Young People of the Second Generation - Bogdan Stańkowski (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The article discusses the problem of the integration of young foreigners, the so called "new Italians" in the Christian context. Italian Salesians implemented a new style of educational work with adolescents/immigrants who moved to Italy from different parts of the world. The first part of the paper emphasizes that the Oratorio has a clear concept of youth's integration with the Christian community based on human values. The second part, including empirical studies conducted in 2016, presents the contemporary efforts of the Salesians/secular tutors in their work with young immigrants.